Comparison between bond crushing energy and fracture energy of rocks in a jaw crusher using numerical simulation - A. Refahi (The Southern African Institute of Mining and Metallurgy, 2009)
For predicting the energy consumption during the size-reduction process, the Bond approach is often used. In this work, the PFC3D discrete element method (DEM) software was employed to model the crushing behaviour of some rocks with different mechanical properties in a laboratory jaw crusher. FLAC3D software was adopted to analyze the stress distribution in the rocks. The rocks studied were modelled as granular assemblies in the shape of a sphere and/or a cube located between two jaws, and the work done by the jaws in the crusher was determined. Nine different types of rocks were studied and the energies consumed by the crusher were compared to those of the Bond comminution energy estimated from the Bond index. There is considerable difference between Bond crushing energy and work done by the jaw crusher for rocks. It appears that the Bond approach is not a suitable method for predicting single particle fracture energy done by the crusher. To verify the results obtained from DEM models, the fracture behaviour of the crushed rocks was examined and was compared to the PFC3D results. The tensile mode of fracturing is favourably modelled by the PFC3D software while the delamination mode cannot be well modelled by PFC3D software. Keywords: jaw crusher; discrete element method; crushing energy; Bond index